Dinamika Diskursus Publik terhadap Penggambaran Kekerasan Seksual pada Film Vina: Sebelum 7 Hari (2024) - Afrida Putri Eskasari; R.A Vita Noor Prima Astuti (Universitas Merdeka Malang, 2025)
The F8 Makassar Festival was organized by the Makassar City Government with the aim of transforming the city's image from one associated with demonstrations into a city known for its festivals. This study seeks to map out the communication activities that took place during the F8 Makassar Festival using a case study approach. The findings reveal that communication activities were primarily focused on publicity and were executed by the Makassar City Communications and Information Agency (Diskominfo) as the government's public relations arm. However, Diskominfo was not involved in message formulation, as its role was outside of the organizing committee. Several publicity strategies were identified, including the use of agenda-setting to construct the image of a “Festival City,” leveraging the political influence of the incumbent mayor to aid publicity efforts, producing efficient content, collaborating with local and regional media, and utilizing the communication networks of the Makassar City Tourism Office (Dispar) and event organizers. No monitoring or evaluation stages were conducted, leaving the success of the city’s transformation into a festival city unclear. Furthermore, the F8 Makassar Festival was not part of a deliberate PR campaign aimed at shaping the